Kalanchoe gideonsmithii (K. subg. Kalanchoe; Crassulaceae subfam. Kalanchooideae), a further new species endemic to the Maputaland-Pondoland Region of Endemism in KwaZulu-Natal, eastern South Africa - Crouch, Neil R.; Figueiredo, Estrela (Phytotaxa, 2022)
The endemic South African species Kalanchoe gideonsmithii (Crassulaceae subfam. Kalanchooideae) is described from KwaZulu-Natal, the eastern-most province of the country. The entire natural geographical distribution range of the species falls within the species-rich Maputaland-Pondoland Region of Endemism. Kalanchoe gideonsmithii is related to K. rotundifolia and K. decumbens, but differs from both by having most plant parts, including the flowers, bluish purple-infused. The leaves of K. gideonsmithii are narrowly oblong, like those of K. decumbens, but longer and of greater diameter than those of the latter species. In contrast, the leaves of K. rotundifolia are mostly oblanceolate to obovate to round in outline. The reproductive morphology of K. gideonsmithii is constant in terms of the size and shape of the corolla tube and lobes, with the distal part of the corolla tube and proximal part of the corolla lobes invariably becoming tightly twisted post-anthesis, as in K. decumbens and K. rotundifolia. At the level of the ovary the corolla tubes of K. gideonsmithii are generally dark orange- to purplish blue-infused, rather than somewhat to distinctly green-infused, as is usually the case in K. rotundifolia and, to a lesser extent, K. decumbens. The upper part of the corolla tube is consistently bright orange-red, with the centres of the adaxial surface of the corolla lobes a similar colour, or sometimes very slightly yellowish-infused in the centre. Kalanchoe gideonsmithii presents a combination of vegetative and reproductive morphological characters that warrants its recognition at species rank, especially following the recent description of the ‘rotundifolioid’ K. waterbergensis and the reinstatement of K. decumbens, also a relative of K. rotundifolia.